On-line coupling of capillary isotachophoresis and zone electrophoresis for the assay of phenolic compounds in plant extracts - Urbánek, Marek; Pospísilová, Marie; Polásek, Miroslav (Electrophoresis, 2002)
The combination of capillary isotachophoresis (ITP) and capillary zone electrophoresis (CZE) in the column coupling configuration was optimized in a mode where the electrolyte for the CZE step is different from the leading and terminating ITP electrolytes. Two colored markers, picric acid and 1-nitroso-2-naphthol, were used for exact timing of the transfer of isotachophoretically stacked analyte zones into the CZE column and for the control of the residual amount of the leading and terminating ITP electrolytes entering the CZE capillary together with the analytes, thus controlling the duration of transient ITP migration in the CZE capillary and ensuring good separation of the analytes and reproducibility of the migration times (relative standard deviations 1%). ITP-CZE was applied to the simultaneous assay of several cinnamic acid derivatives and flavonoids in methanolic extracts of Sambucus flowers and Crataegus leaves and flowers. The preconcentrating and cleansing effect of the ITP step allowed injection of relatively large sample volumes (30 microL). The limits of detection were approximately 20-50 ng x mL(-1) and 100 ng x mL(-1) for the acids and flavonoids, respectively ( thick similar 200-times lower compared to conventional CE) with spectrophotometric detection at 254 nm. The ITP-CZE exhibited satisfactory linearity and precision when using CZE buffer of pseudo "pH" 9.0; 1-nitroso-2-naphthol was employed as the internal standard. The separation took approximately 35 min. The ITP-CZE results for rutin, hyperoside, and vitexin-2-O"-rhamnoside were in good accordance with those obtained previously by high-performance liquid chromatography.
Keywords: elektrolyty; Electrophoresis; Electrophoresis, Capillary; elektroforéza; Phenols; Plant Extracts; elektroforéza kapilární; fenoly; rostlinné extrakty; Electrolytes